2021
DOI: 10.22363/2313-1683-2021-18-1-235-253
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Addiction and Personality: Review of International Research

Abstract: Mobile phones are perhaps the most popular digital devices that accompany us all the time. Smartphones certainly provide us with many conveniences but at the same time these devices are the reason why many users develop a pathological condition known as nomophobia or smartphone addiction, i. e., fear of losing phone contact or being away from network coverage. Many people, especially teenagers and children, cannot imagine their life without smartphones and try never to part with them. Phone addicts, due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…On the one hand, as high school students who are addicted to mobile phones are more exposed to virtual Internet environments and thus receive more hostile messages on the Web ( Alvarez-Garcia et al, 2015 ; HwaJin and Wanju, 2021 ). On the other hand, mobile phone-addicted teens exhibit higher levels of emotional problems and social dysfunction problems ( Jain and Agrawal, 2020 ; Sheinov, 2021 ), is more likely to be targeted for cyber violence. Moreover, the anonymity of cyberbullying increases the negative impact of bullying victims by preventing them from judging the source of bullying, and non-face-to-face communication prevents victims from venting the negative emotions generated by bullying, thereby increasing their level of depression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, as high school students who are addicted to mobile phones are more exposed to virtual Internet environments and thus receive more hostile messages on the Web ( Alvarez-Garcia et al, 2015 ; HwaJin and Wanju, 2021 ). On the other hand, mobile phone-addicted teens exhibit higher levels of emotional problems and social dysfunction problems ( Jain and Agrawal, 2020 ; Sheinov, 2021 ), is more likely to be targeted for cyber violence. Moreover, the anonymity of cyberbullying increases the negative impact of bullying victims by preventing them from judging the source of bullying, and non-face-to-face communication prevents victims from venting the negative emotions generated by bullying, thereby increasing their level of depression.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the study suggests that adolescents with problematics mobile phone use are more exposed to cyberbullying ( Mendez et al, 2020 ; Sheinov, 2021 ; Smale et al, 2021 ). Cyberbullying refers to aggressive and hostile attacks by a group or individual using electronic media, especially mobile phones or the Internet, repeatedly and permanently against victims who cannot easily protect themselves ( Smith et al, 2008 ; Lim, 2013 ; Kowalski et al, 2014 ; Costa et al, 2019 ).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“… 14 Several researchers have suggested that smartphone addiction is a new phenomenon, and one of the most common non-medical addictions. 16 Presently, smartphones have become indispensable in many people's lives. To avoid the risk of addiction, reluctance to indulge in the use of smartphones has arisen.…”
Section: Smartphone Addictionmentioning
confidence: 99%
“…Nonetheless, excessive Internet use may impede development, harm mental health and social functioning, and even lead to addiction (Chao, et al, 2020). Besides, research indicates that adolescents who use the Internet excessively are susceptible to cyberbullying (Mendez, et al, 2020;Sheinov, 2021). Teenagers are particularly prone to cyberbullying.…”
Section: Introductionmentioning
confidence: 99%